2004
DOI: 10.1002/ejic.200300396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Stepwise Dissociation of FeIII Complexes with Tripodal Ligands as Siderophore Models

Abstract: The acid hydrolysis and formation kinetics of 1:1 ferric complexes with several tripodal hexadentate ligands were investigated over the [H + ] range of 0.02−1.0 M at 25°C and at an ionic strength of 2.0 M (NaClO 4 /HClO 4 ). These ligands are based on a tris(2-aminoethyl)amine (TREN) spacer connected through a tris(amide) moiety to identical pendant bidentate chelating group arms such as catecholate (TREN-CAMS,Mixed ligands with chelating arms such as catecholate and 8-hydroxyquinolinate (TRENSOX2CAMS, L 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Thus, the coordination number of DFB to the Fe center in the ternary complex is less than that for the FeDFB complex. In addition, the previous study by Serratrice et al (2004) indicated that the spectral shape of Fe and the model siderophore complex (including catecholate and hydroxamate groups) is affected by the coordination number at the Fe center (e.g., the hexadentate and tetradentate complexes) as well as the mode of coordination associated with ligand protonation. Therefore, our observation that the absorbance spectra (300-600 nm) in the ligand exchange experiment are almost analogous (homothetic) to that for FeDFB suggests little effect of ternary complexes on the FeDFB measurement (Fig.…”
Section: Ligand Exchange Experimentsmentioning
confidence: 96%
“…Thus, the coordination number of DFB to the Fe center in the ternary complex is less than that for the FeDFB complex. In addition, the previous study by Serratrice et al (2004) indicated that the spectral shape of Fe and the model siderophore complex (including catecholate and hydroxamate groups) is affected by the coordination number at the Fe center (e.g., the hexadentate and tetradentate complexes) as well as the mode of coordination associated with ligand protonation. Therefore, our observation that the absorbance spectra (300-600 nm) in the ligand exchange experiment are almost analogous (homothetic) to that for FeDFB suggests little effect of ternary complexes on the FeDFB measurement (Fig.…”
Section: Ligand Exchange Experimentsmentioning
confidence: 96%
“…Proposed structures for the transition states and rates of coordination bonds cleavage in the complexes should be helpful for designing new ligands for appropriate Fe(III) exchange in biological systems (Albrecht & Crumbliss 1998). Analysis of kinetic data for the acid dissociation kinetics of the Fe(III) complexes with a series of tripodal ligands (Serratrice et al 2004) shown that there is a common mechanism in all the series when the ligand structure varies. The acid hydrolysis reaction was found to proceed via a stepwise mechanism.…”
Section: Kinetic Studies and Exchange Reactionsmentioning
confidence: 97%
“…In a previous investigation on the acid dissociation kinetics of the Fe III complexes with these tripodal ligands, we observed a very fast dissociation of one arm of the ligand which is maintained in proximity to the first coordination sphere of Fe III . [10] This indicates that the complex has one labile arm thus favoring the formation of the precursor complex and then the substitution by one arm of the competing ligand. So, it is reasonable to propose that the kinetic rate constant k 1 represents the substitution rate of one arm of the initial complex by one arm of the competing ligand.…”
Section: Discussionmentioning
confidence: 98%